PEMBUATAN IKLAN “KERUPUK ASOYBIG” UNTUK PENINGKATAN BRAND EQUITY - Sifa Sultanika (P3M Politeknik Negeri Media Kreatif, 2024)
A product must have strategic value increasing sales and brand equity, including Small Medium Enterprises products. In making this advertisement by highlighting the local product Asoy crackers from Bogor, the author wanted to make the advertisement a promotional medium that he felt was appropriate and could increase brand equity. The advantage of making this advertisement is that previously there was no promotional media that specifically promoted Asoy cracker products as a snack from this rainy city. This advertisement with the title “Asoybig Crackers” was created based on research results and the manufacture’s needs for a wider consumer reach by including this adverstisement on the Youtube channel or website that has been created. The method used in making this video is data collection, carrying out SMART analysis and brainstorming to make the video. Promotion of a product to increase brand equity using digital promotional media is expected to provide an increase in local products, especially Asoy crackers.